MICROBIAL RESILIENCE UNDER ENVIRONMENTAL STRESS: A SYSTEMS-LEVEL ANALYSIS OF METABOLIC AND GENOMIC ADAPTATION - Achmad Agus Salim; Li Wei; Emily Johnson (Research of Scientia Naturalis, 2026)
Microbial resilience under environmental stress represents a fundamental aspect of biological survival, shaped by complex interactions between metabolic processes and genomic adaptation. Increasing environmental pressures such as temperature fluctuation, oxidative stress, and nutrient limitation challenge microbial stability, yet existing studies often examine metabolic and genetic responses in isolation. This study aims to develop a systems-level framework that integrates metabolic and genomic dimensions to explain how microorganisms sustain functionality under stress. The research employs a mixed-methods design combining laboratory-based multi-omics data, secondary datasets, and nonlinear computational modeling to analyze adaptive responses across temporal phases. Results indicate that microbial resilience is governed by coordinated mechanisms involving rapid metabolic reprogramming and subsequent genomic modification, with nonlinear dynamics such as threshold effects and multi-stable states shaping system behavior. Gene expression, metabolite flux, and mutation frequency exhibit strong interdependence, revealing feedback-driven adaptation rather than linear response patterns. The findings demonstrate that resilience emerges as a dynamic and context-sensitive process rather than a static trait. The study concludes that integrating ecological, metabolic, and genomic perspectives through nonlinear modeling significantly enhances the understanding of microbial adaptation and provides a robust analytical framework for future research and applied sciences.